Therapeutic Use of Agonists of the Nuclear Receptor PPARγ in Alzheimer's Disease - Landreth, Gary (Current Alzheimer Research, 2007)
Alzheimer's disease (AD) is a devastating neurodegenerative disease for which there are no highly effective therapies. A novel therapeutic approach to the treatment of AD is the use of agonists of the nuclear receptor, peroxisome proliferators-activated receptor gamma (PPARγ). PPARγ is a ligand activated transcription factor whose best described roles are to regulate lipid metabolism and inflammation. Agonists of PPARγ have been shown to ameliorate AD-related pathology in animal models of AD and improve cognition. A number of potential mechanisms have been advanced to account for these effects. PPARγ agonists act as insulin sensitizers, facilitating insulin action. In addition, PPARγ agonists have been shown to inhibit inflammatory gene expression, alter A β homeostasis and exhibit neuroprotective effects. Importantly, recent clinical trials of FDA approved PPARγ agonists have been shown to improve cognition and memory in AD patients. Thus, PPAR agonists represent a new and potentially efficacious treatment of AD.
Keywords: beta amyloid